System Responsiveness to the Psychosocial and Mental Health Needs of Children in Ethiopian Primary Schools: The Case of Gondar City, Northwest Ethiopia Needs - Wondie, Yemataw; Tadele, Tesfaye (Frontiers in Sociology, 2021)
Background: Ethiopia is the second most populous nation in Africa with children and adolescents constituting more than 40% of the population. Evidence shows the onset of significant degrees of mental illnesses is detectable in this age range. For such early identification to be made there should be a system responding to those needs. Objective: The objective of this study was to explore the extent to which the education system is responsive to the psychosocial and mental health needs of children in primary schools through putting appropriate professionals in place, raising teachers’ awareness and putting in place viable policies and guidelines. Methods: An exploratory qualitative study was conducted in public and private primary schools in Gondar city Data was collected through focus group discussions from seventeen participants drawn from both schools and key informant interviews with two experts from the zonal Department of Education. A thematic qualitative data analysis was employed. Themes were identified with the help of the Nvivo 12 plus software. Results: We found teachers’ mental health awareness is very low with parameters such as magnitude, case identification and support. There is an exception in terms of causal attributions of mental illness that matches with scientific literature. Psychosocial support and mental health resources are not available and schools do not provide capacity building mental health trainings for teachers which might help them to identify, handle and make referrals of mental health cases. We also found the Ethiopian education policy and other guidelines do not address the issue of mental health at primary school level. Conclusion: The Ethiopian education system is not responsive to the psychosocial and mental health needs of children in primary schools. Implications: Arresting minor impairments before they become major disabilities is vital. Investing in childhood mental health enables a healthy and productive society to be cultivated. The Ethiopian education system should therefore respond to the psychosocial and mental health needs of children in primary schools.